Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd010245
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid for reducing mortality in emergency and urgent surgery

Abstract: Tranexamic acid for reducing mortality in emergency and urgent surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
69
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 9 publications
0
69
2
2
Order By: Relevance
“…A Cochrane review showed that TXA significantly reduces blood transfusion in patients undergoing emergency or urgent non-obstetrical surgery. 18 TXA is safe in pregnancy, being FDA category B. It is therefore unsurprising that there is interest in its role in the prevention of postpartum hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review showed that TXA significantly reduces blood transfusion in patients undergoing emergency or urgent non-obstetrical surgery. 18 TXA is safe in pregnancy, being FDA category B. It is therefore unsurprising that there is interest in its role in the prevention of postpartum hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…45 Nonetheless, because available clinical trials as a whole 10 include a small number of TXA-treated patients, some doubt persists regarding the safety of TXA. [46][47][48] The European Society of Anaesthesiology guidelines 39 recommend TXA administration in total hip and knee arthroplasty and in spine surgery. However, these recommendations are accompanied by the sug-15 gestion to individually evaluate the risk-benefits of the treatment in women, patients with a history of VTE, and individuals older than 60 yr.…”
mentioning
confidence: 99%
“…A number of Cochrane systematic reviews conducted in a variety of surgical settings had reported the efficacy of prophylactic perioperative administration of TXA in reducing blood loss and the need for blood transfusion. [6][7][8][9][10] TXA has already been demonstrated to reduce uterine blood loss in non-surgical aspect. Various studies had revealed that TXA resulted in a significant reduction of menstrual blood loss in menorrhagic women while not increasing the risk of thrombosis and had been used successfully to treat menorrhagia associated with a number of coagulopathies.…”
mentioning
confidence: 99%
“…26 There has been consistent results about the significant role of TXA in blood conservation in various settings, from trauma to cardiac, neurological, orthopedic, craniofacial, obstetric and gynaecological surgery. [6][7][8]27 Ker et al in their systematic review of randomized clinical trials on the effect of TXA on surgical blood loss had revealed that TXA reduces the probability of blood transfusion by 38%. 16 With growing evidence about the positive effects of TXA on perioperative bleeding and transfusion rate, this randomized, double-blinded, placebo-controlled study was conducted with the objective of determining whether a single prophylactic dose of TXA given intravenously can reduce perioperative blood loss and also the need for blood transfusion in patients undergoing abdominal hysterectomy.…”
mentioning
confidence: 99%
See 1 more Smart Citation